SOSIALISASI DAN AKSI BERSIH PANTAI SEBAGAI UPAYA MENGURANGI SAMPAH DAN PENCEGAHAN PENYAKIT - ida, Wahidanur; Khairol, T. Khairol Razi; Isni, Isni Hijriana (Yayasan Sagita Akademia Maju, 2023)
Active community activities can help keep the beach clean. As members of the community, beach visitors must also participate in beach cleaning, such as throwing rubbish in its place. Beach cleanliness that is not maintained will result in environmental pollution and can cause disease. The aim of this community service activity is to maintain beach cleanliness and raise awareness among the public and beach visitors about the benefits of beach cleanliness. The activity implementation method consists of three stages, namely the preparation, implementation and evaluation stages. As a result of the activities, the beach environment is clean, beautiful and there is no longer the smell of accumulated rubbish. It is hoped that the local community and visitors will always maintain the cleanliness of the beach.